2013
DOI: 10.2754/avb201382010055
|View full text |Cite
|
Sign up to set email alerts
|

The impact of using lead pellets on lead contamination of mallards (Anas platyrhynchos) in the Czech Republic

Abstract: The aim of the study was to assess the degree of lead contamination in mallards in the Czech Republic as a result of using lead shots for wildfowling. Two sites used for mallard hunting were chosen, namely a flood-control reservoir in Moravia and a small fishpond in Bohemia. Lead concentrations were determined in the tissues of 20 mallards (Anas platyrhynchos) raised at those standing open water sites (n = 10 at each site) and killed there during the autumn hunting season with a steel shot. Control groups were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…On the contrary, the comparison to ducks collected in the Warmia and Mazury region (North Poland) showed that birds from Zator accumulated higher amount of lead in liver and muscles (Szymczyk and Zalewski, 2003). In relation to Mallards studied in other parts of Europe, birds from Southern Poland accumulated comparable amount of lead in liver, bigger ones in kidneys and smaller in bones and muscles (Gasparik et al, 2010;Hutařová et al, 2013). According to the research from the USA, the Zator ducks revealed similar Pb levels in kidneys, but higher ones in liver and bones.…”
Section: Lead Concentrations In Tissuesmentioning
confidence: 85%
“…On the contrary, the comparison to ducks collected in the Warmia and Mazury region (North Poland) showed that birds from Zator accumulated higher amount of lead in liver and muscles (Szymczyk and Zalewski, 2003). In relation to Mallards studied in other parts of Europe, birds from Southern Poland accumulated comparable amount of lead in liver, bigger ones in kidneys and smaller in bones and muscles (Gasparik et al, 2010;Hutařová et al, 2013). According to the research from the USA, the Zator ducks revealed similar Pb levels in kidneys, but higher ones in liver and bones.…”
Section: Lead Concentrations In Tissuesmentioning
confidence: 85%
“…Muscle lead concentrations in wild birds and small mammals that are not lead poisoned and have not been killed using lead gunshot are low, usually below 0.100 ppm w.w. (e.g. Koréneková et al 2008 ; Damerau et al 2013 ; Hutařová et al 2013 ). Biologically incorporated lead consists of lead which has been absorbed into the bloodstream, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The lead particles can be widely dispersed in the carcass and undetectable by eye, and bioavailable to humans (Hunt et al 2009, Schulz et al 2021 a ). In the absence of lead ammunition, game meat contains some level of lead from natural and anthropogenic sources, albeit at lower levels (Koréneková et al 2008, Hutařová et al 2013). However, consumption of meat contaminated with particles of ammunition‐derived lead can lead to elevated blood lead levels with commensurate health risks (Green and Pain 2019).…”
Section: Drivers Of Changementioning
confidence: 99%